Radiation-induced synthesis of nanoscale Co- and Ni-based electro-catalysts on carbon for the oxygen reduction reaction. Issue 30 (20th July 2017) - Soroka, Inna L.; Tarakina, Nadezda V.; Hermansson, Anton; Bigum, Lukas; Widerberg, Rickard; Andersson, Mikael S.; Mathieu, Roland; Paulraj, Alagar R.; Kiros, Yohannes
Abstract : A facile synthesis of 3d-metal based electro-catalysts directly incorporated into a carbon support was carried out by γ-radiation. Abstract : A facile synthesis of 3d-metal based electro-catalysts directly incorporated into a carbon support was carried out by γ-radiation. Transition metals of period 4, i.e. Ni and Co, were precipitated and reduced from their respective salt solutions. The obtained materials were characterized by XRD, SEM, SQUID and the BET methods. Thereafter, the electrodes for fuel cells were fabricated out of synthesized material and their electrochemical performance for the oxygen reduction reaction in 6 M KOH was measured. Although the concentrations of Co and Ni in the electrode material were low (3.4% Co and 0.4% Ni) after reduction by irradiation, both the Ni and Co-based gas diffusion electrodes showed high catalytic activity for oxygen reduction both at room temperature and at 60 °C.